Traffic Information Acquisition System with Ultrasonic Sensors in Wireless Sensor Networks. (21st May 2014) - Jo, Youngtae; Choi, Jinsup; Jung, Inbum
Abstract : Existing systems for traffic information acquisition have high costs and low scalability owing to their characteristics such as large size, wired power supplies, and wired communication. To achieve low costs and high scalability, the use of traffic information acquisition systems based on wireless sensor networks (WSNs) has been suggested. However, WSN-based systems have important issues, such as low computing power, limited battery capacity, and high transmission delay. Existing studies on WSN-based acquisition systems have not considered all three of these problems together. Moreover, most studies have focused on theoretical problems rather than practical ones. Therefore, we propose a new system that considers all three limitations of WSN-based systems. In our experiments, we installed our system on real roads for an accurate evaluation. The results show that our system has a high detection accuracy, low power consumption, and low transmission delay.